'Wiser than thy sire': Youth and Age in Emily Brontë's Poetry. (2nd April 2020) - Cook, Peter
Abstract : A significant number of Emily Brontë's poems explore the contrasting states of youth and age. In most of them Brontë creates a dialogue between personae representing the two states, and calls into question traditional moral values by examining the relationship between her personae and the natural world. Her conclusions and ways of working in these poems, and in Wuthering Heights, formed a seminal conduit between the ideas of Romantic writers and the mid-nineteenth century, and at the same time achieved a radical reworking of these ideas and values for her own time and place.